Supply chains and credit-market shocks: Some implications for emerging markets - Yothin Jinjarak (Asian Development Bank Institute (ADBI), 2013)
Driven by the increasingly important role of supply chains in global production, this paper studies empirical association between global credit-market shocks and firm behavior towards liquidity needs across countries and industries. Focusing on the adjustment of working-capital financing, we find two pieces of supporting evidence from international firm-level panel data covering the period 2002:I - 2012:IV. First, for industries where specific investment in the input supplier-customer relationship is large, firms are more exposed to credit-market shocks. We find that measures of global credit-market shocks are negatively associated with trade receivables, trade payables, and inventories, conditional on the level of contract intensity in the industries where firms operate. Second, firms in emerging markets are more vulnerable to credit-market shocks than are firms in developed countries. We are also able to verify the economic significance of sales growth, operating cash flows, cash stock, and firm size in the overall adjustment. Our findings highlight the importance of balance-sheet contagion along supply chains during the 2007- 09 global financial crisis.
Keywords: G14; E0; F0; 330; balance-sheet contagion; trade credit; differentiated products; financial system efficiency; supply chains; Nettoumlaufvermögen; Unternehmensfinanzierung; Finanzkrise; Internationale Arbeitsteilung; Schätzung